Analisis Pengembangan Sumber Daya Manusia terhadap Assessment Center Pegawai Negeri Sipil pada Kantor Distrik Karas Kabupaten Fakfak - Agustina Waromi; Maria Wesso (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to analyze the development of human resources in relation to the assessment center for Civil Servants (PNS) at the Karas District Office, Fakfak Regency. The objectives of this study are to determine the effect of human resource development on the assessment center, and to identify the human resource development variables that most dominantly influence the PNS assessment center. This research uses a qualitative approach with data collection methods including interviews, observations, questionnaires, surveys, and experiments. The data were analyzed qualitatively and quantitatively to explain the relationship between human resource development and the assessment center. The qualitative analysis results show that PNS at the Department of Mining and Energy, Fakfak Regency, who hold Echelon IV/a structural positions, number 15 people (0.71%), while PNS with the rank of Pembina Level I/IV/b number 5 people (0.24%). Based on gender, the majority of PNS are male (15 people or 0.71%) who have participated in human resource development through career development. PNS with a Bachelor's degree (S-1) number 11 people (0.52%), and those aged 41-50 years and over 50 years number 12 people (0.57%).